Resin composition for sealing optical semiconductor, resin molded article for sealing optical semiconductor, optical semiconductor sealing material, and optical semiconductor device
By using a resin composition for optical semiconductor packaging with a high biomass ratio, containing diols from plants, and using specific molding and curing methods, the problems of oil resource consumption and CO2 emissions in the prior art are solved, and an environmentally friendly packaging material with high light transmittance and heat resistance are achieved.
Patent Information
- Application Number
- CN202411082041.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-09
- Filing Date
- 2024-08-08
- Publication Date
- 2025-02-25
AI Technical Summary
The conventional resin composition for optical semiconductor packaging is composed of petroleum materials, and there are problems of oil resource depletion and CO2 emissions.
A resin composition for optical semiconductor packaging with a biomass ratio of more than 10% was developed, including diols from plants, and cured bodies with high light transmittance and heat resistance were prepared by specific molding and curing methods.
It realizes environmentally friendly optical semiconductor packaging materials, reduces the consumption of petroleum resources and CO2 emissions, and improves the light transmittance and heat resistance of the materials.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition for optical semiconductor encapsulation, a resin molded product for optical semiconductor encapsulation, an optical semiconductor encapsulation material and an optical semiconductor device. Background Art
[0002] Optical semiconductor elements are packaged in ceramic packages or plastic packages to form devices. Here, the constituent materials of ceramic packages are relatively expensive and have poor mass production, so plastic packages have become the mainstream. Among them, from the perspectives of workability, mass production, and reliability, the technology of pre-pressing an epoxy resin composition into a tablet shape and performing transfer molding on the obtained molded product has become the mainstream.
[0003] Conventional optical semiconductor encapsulation resin compositions are composed of petroleum-derived materials (eg, Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application No. 2021-528503 Summary of the invention
[0007] Problems to be solved by the invention
[0008] Conventional optical semiconductor encapsulation resin compositions are composed of petroleum-derived materials. 2 From an emissions perspective, there is room for improvement.
[0009] The present invention solves the above-mentioned problems newly discovered by the inventors of the present application, and aims to provide an environmentally friendly optical semiconductor encapsulation resin composition, and an optical semiconductor encapsulation resin molded product, an optical semiconductor encapsulation material and an optical semiconductor device using the optical semiconductor encapsulation resin composition.
[0010] Means used to solve problems
[0011] The present invention (1) relates to a resin composition for optical semiconductor encapsulation, wherein the biomass ratio of the resin composition for optical semiconductor encapsulation is 10% by mass or more.
[0012] The present invention (2) relates to the resin composition for optical semiconductor encapsulation according to the present invention (1), wherein the resin composition for optical semiconductor encapsulation contains a plant-derived diol.
[0013] The present invention (3) relates to the resin composition for optical semiconductor encapsulation according to the present invention (2), wherein the diol is a diol having hydroxyl groups at both ends of the main chain.
[0014] The present invention (4) relates to the resin composition for optical semiconductor encapsulation according to the present invention (2) or (3), wherein the diol is a polymer.
[0015] The present invention (5) relates to the resin composition for optical semiconductor encapsulation according to any one of the present inventions (1) to (4), wherein when the resin composition is cured (size: cylindrical, 50 mm in diameter x 1 mm in thickness) by the following method, the linear transmittance at a wavelength of 400 nm is 50% or more,
[0016] (Method for producing a solidified body)
[0017] Using a transfer molding machine, the heated and molten resin composition is extruded into a molding mold heated to 150°C±5°C by transfer molding under pressure, and is cured for 4 minutes without any voids inside to obtain a uniform cured body; then the uniform cured body is taken out from the mold, and is heated in a dryer at 150°C for 3 hours to completely cure it, thereby obtaining a cured body.
[0018] The present invention (6) relates to a resin composition for optical semiconductor encapsulation as described in any one of the present inventions (1) to (5), wherein the cured body (size: cylindrical with a diameter of 50 mm and a thickness of 1 mm) obtained by the method is subjected to three reflow processes at 265°C, and has a linear transmittance of 50% or more at a wavelength of 400 nm.
[0019] The present invention (7) relates to the resin composition for optical semiconductor encapsulation according to any one of the present inventions (1) to (6), wherein the glass transition temperature of the cured product (size: cylindrical with a diameter of 50 mm and a thickness of 1 mm) obtained by the method is above 0°C.
[0020] The present invention (8) relates to the resin composition for optical semiconductor encapsulation according to any one of the present inventions (1) to (7), wherein the resin composition for optical semiconductor encapsulation is used for transfer molding.
[0021] The present invention (9) relates to a resin molded product for optical semiconductor encapsulation, comprising the resin composition for optical semiconductor encapsulation according to any one of the present inventions (1) to (8).
[0022] The present invention (10) relates to an optical semiconductor encapsulation material obtained by molding the optical semiconductor encapsulation resin molded product according to the present invention (9).
[0023] The present invention (11) relates to an optical semiconductor device comprising: an optical semiconductor element; and the optical semiconductor encapsulating material according to the present invention (10) for encapsulating the optical semiconductor element.
[0024] Effects of the Invention
[0025] The resin composition for optical semiconductor encapsulation of the present invention has a biomass ratio of 10% by mass or more and is therefore environmentally friendly. DETAILED DESCRIPTION
[0026] The biomass ratio of the optical semiconductor encapsulation resin composition of the present invention is 10% by mass or more. This is environmentally friendly, can suppress the depletion of petroleum resources, and can also reduce CO 2 Emissions.
[0027] In this specification, the biomass ratio refers to the content of carbon from organisms. Carbon from organisms contains a certain proportion of radioactive isotopes (C-14), while carbon from petroleum contains almost no C-14. Therefore, the biomass ratio can be calculated by measuring the concentration of C-14 contained in the measurement object. In this specification, the biomass ratio is measured according to ASTM D6866-22, a standard used in the bioplastics industry.
[0028] In the present specification, when a numerical range is expressed with "-" such as 50 mass % to 100 mass %, the upper limit and the lower limit are included. For example, 50 mass % to 100 mass % means 50 mass % or more and 100 mass % or less.
[0029] <Resin composition for optical semiconductor encapsulation>
[0030] For the optical semiconductor encapsulation resin composition of the present invention, the biomass ratio (the content of carbon from organisms) is 10% by mass or more, preferably 10% to 50% by mass, more preferably 10% to 30% by mass, and further preferably 10% to 20% by mass. The larger the biomass ratio, the more the environmental load can be reduced. Although there is no particular limit to the upper limit of the biomass ratio, the current situation is that among the raw materials used in the optical semiconductor encapsulation resin composition, there are only limited raw materials such as diols from biological raw materials, so the above upper limit is preferably the above-mentioned upper limit. When the biomass ratio is greater than 50% by mass, the thermal reaction is hindered, and it is difficult to adjust the degree of reactivity, which may lead to a reduction in crushing / tabletting properties. In addition, uncured problems may also occur.
[0031] The resin composition for optical semiconductor encapsulation having a biomass ratio within the above range can be achieved by using raw materials from organisms, such as diols from organisms, preferably diols from plants. In addition, it can also be achieved by using raw materials having an isosorbide structure described later. These can be used alone or in combination of two or more.
[0032] The diol and the raw material having an isosorbide structure are preferably diols having hydroxyl groups at both ends of the main chain, which tends to adjust the glass transition temperature and further improve light transmittance and heat resistance.
[0033] The diol and the raw material having an isosorbide structure are preferably polymers, and more preferably polymers having hydroxyl groups at both ends of the main chain, which tends to adjust the glass transition temperature and further improve light transmittance and heat resistance.
[0034] <<Biologically derived glycols>>
[0035] In the section "Biologically derived diols", one specific example of biologically derived diols is described. In this section, biologically derived diols other than the raw material having an isosorbide structure described later are described.
[0036] Examples of bio-derived diols include polytetramethylene ether glycol (PTMG) and the like. These can be used alone or in combination of two or more. Among them, polytetramethylene ether glycol is preferred. Bio-derived polytetramethylene ether glycol is synthesized by ring-opening tetrahydrofuran derived from plants.
[0037] Polytetramethylene ether glycol is a polymer represented by the following formula (B), and is a diol having hydroxyl groups at both ends of the molecular chain.
[0038]
[0039] (In formula (B), m is the number of repeating units.)
[0040] The number average molecular weight of a bio-derived diol such as polytetramethylene ether glycol is preferably 100 to 5000, more preferably 500 to 2000, and even more preferably 600 to 900. This tends to further improve light transmittance and heat resistance.
[0041] In this specification, the number average molecular weight is a value determined by measuring by gel permeation chromatography (GPC) and converting it into polystyrene.
[0042] The hydroxyl value of bio-derived diols such as polytetramethylene ether glycol is preferably 50 to 300 mgKOH / g, more preferably 100 to 250 mgKOH / g, and even more preferably 130 to 200 mgKOH / g, which tends to further improve light transmittance and heat resistance.
[0043] In the present specification, the hydroxyl value refers to the hydroxyl value described in JIS K 0070: 1992, that is, the number of mg of potassium hydroxide required to neutralize acetic acid bonded to hydroxyl groups when 1 g of a sample is acetylated.
[0044] In 100% by mass of the optical semiconductor encapsulation resin composition, the proportion of bio-derived diols such as polytetramethylene ether glycol (excluding raw materials having an isosorbide structure) is preferably 5% to 90% by mass, more preferably 5% to 21% by mass, and further preferably 5% to 15% by mass. This tends to further improve light transmittance, heat resistance, crushability, and tablet formability.
[0045] <<Raw materials with isosorbide structure>>
[0046] The raw material having an isosorbide structure is described. In the present specification, the isosorbide structure refers to a structure derived from isosorbide (a compound represented by the following formula (1-1)), specifically, a structure represented by the following formula (1-2). Therefore, the raw material having an isosorbide structure may have a structure represented by the following formula (1-2), and in addition to the compound represented by the following formula (1-1), it also includes, for example, a structural unit derived from isosorbide (a unit represented by the following formula (1-3) in the following formula (1-3) is a compound having a connecting bond).
[0047]
[0048]
[0049]
[0050] The isosorbide structure of the raw material having an isosorbide structure is preferably a structure derived from isosorbide from a living organism, and more preferably a structure derived from isosorbide from a plant. By using a raw material using a biomass material (material from a living organism, etc.) as the raw material having an isosorbide structure, the environmental load can be reduced.
[0051] As a raw material having an isosorbide structure, there is no particular limitation as long as it has an isosorbide structure. Specific examples of raw materials having an isosorbide structure include: isosorbide; polymers having structural units derived from isosorbide; isosorbide derivatives obtained by giving substituents to isosorbide such as isosorbide having an epoxy group and isosorbide having a hydroxyl group; isosorbide glycidyl ether, etc. These can be used alone or in combination of two or more. Among them, polymers and isosorbide derivatives having structural units derived from isosorbide are preferred, and polymers having structural units derived from isosorbide are more preferred. In addition, as an isosorbide derivative, isosorbide having an epoxy group is preferred.
[0052] The raw material with isosorbide structure is preferably a polyol. This has a tendency to adjust the glass transition temperature and further improve light transmittance and heat resistance. As long as the polyol is a compound with more than two hydroxyl groups, it is preferably a diol (glycol). That is, the raw material with isosorbide structure is preferably a compound with more than two hydroxyl groups, more preferably a diol (glycol). The isosorbide structure of the raw material with isosorbide structure is a structure derived from isosorbide from a living thing, and when the raw material with isosorbide structure is a diol, it belongs to a diol from a living thing.
[0053] As a polymer having a structural unit derived from isosorbide, for example, it can be listed: a homopolymer (isosorbide homopolymer) in which all structural units are composed of structural units derived from isosorbide; a copolymer (isosorbide copolymer) having structural units derived from isosorbide and other structural units, etc. These can be used alone or in combination of two or more. When using an isosorbide homopolymer, although the compatibility with other compounding agents can be improved, there is a possibility that the molecular weight of the cured product cannot be fully increased. On the other hand, when using an isosorbide copolymer, there is a tendency that the molecular weight of the cured product also fully increases while improving the compatibility with other compounding agents. Therefore, as a polymer having a structural unit derived from isosorbide, an isosorbide copolymer is preferred. The copolymer can be a block polymer or a random polymer.
[0054] As other structural units (structural units other than structural units derived from isosorbide) possessed by the isosorbide copolymer, for example, structural units derived from alkane diols and the like can be cited. These can be used alone or in combination of two or more. Among them, structural units derived from alkane diols are preferred. That is, as a polymer having structural units derived from isosorbide, it is preferred to have structural units derived from isosorbide and structural units derived from alkane diols, and it is more preferred to have structural units derived from isosorbide and structural units derived from alkane diols and have hydroxyl groups at both ends.
[0055] The polymer having a structural unit derived from isosorbide and a structural unit derived from an alkane diol is not particularly limited as long as it has these two structural units, but a polymer represented by the following formula (A) is preferred. The polymer represented by the following formula (A) is a diol having hydroxyl groups at both ends of the molecular chain.
[0056]
[0057] (In formula (A), a plurality of Rs are structural units derived from isosorbide or structural units derived from alkane diol, and the polymer has at least one of these two structural units. n is the number of repeating units.)
[0058] Specific examples of the structural unit derived from isosorbide include the unit represented by the following formula (1-3): Specific examples of the structural unit derived from an alkanediol include a divalent alkylene group formed from an alkane of an alkanediol.
[0059]
[0060] Alkane diol refers to a polyol having two hydroxyl groups. Alkane diols can be used alone or in combination of two or more. The position of the hydroxyl group possessed by the alkane is not particularly limited, and preferably at least one hydroxyl group is located at the end of the main chain of the alkane chain, and more preferably both hydroxyl groups are located at the end of the main chain of the alkane chain (having hydroxyl groups at both ends of the main chain of the alkane chain). For example, 1,6-hexanediol and 3-methyl-1,5-pentanediol are diols having hydroxyl groups at both ends of the main chain of the alkane chain, and 1,2-hexanediol is a diol having a hydroxyl group at one end of the main chain of the alkane chain.
[0061] The number of carbon atoms in the alkane diol is preferably 1 to 10, more preferably 2 to 9, and even more preferably 3 to 7. This tends to further improve light transmittance and heat resistance.
[0062] Examples of the alkane of the alkane diol include normal alkanes such as n-propane, n-butane, n-pentane, n-hexane, n-heptane, and n-octane; isoalkanes such as isobutane, isopentane, 2-methylpentane, 2-methylhexane, and 2,2,4-trimethylpentane; etc. These can be used alone or in combination of two or more. Among them, normal alkanes are preferred, and n-propane, n-butane, n-pentane, n-hexane, and n-heptane are more preferred.
[0063] The alkane diol is preferably a diol having hydroxyl groups at both ends of the main chain of a normal alkane chain, more preferably 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,7-heptanediol, and still more preferably 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.
[0064] As mentioned above, the structural unit derived from alkane diol is a divalent alkylene group formed from the alkane of the alkane diol, so those skilled in the art can read the aforementioned preferred form of alkane diol in another way as a preferred form of alkylene.
[0065] The ratio of the structural unit derived from isosorbide in the polymer having the structural unit derived from isosorbide and the structural unit derived from the alkane diol is preferably 20% to 70% by mass, more preferably 35% to 55% by mass, based on 100% by mass of the polymer. This tends to further improve light transmittance and heat resistance.
[0066] The ratio of the structural unit derived from the alkane diol in the polymer having the structural unit derived from isosorbide and the structural unit derived from the alkane diol is preferably 30% to 80% by mass, more preferably 45% to 65% by mass, based on 100% by mass of the polymer. This tends to further improve light transmittance and heat resistance.
[0067] The total ratio of the structural unit derived from isosorbide and the structural unit derived from the alkane diol in the polymer having the structural unit derived from isosorbide and the structural unit derived from the alkane diol is preferably 98% by mass or more in 100% by mass of the polymer, and may be 100% by mass. This tends to further improve light transmittance and heat resistance.
[0068] In the present specification, the ratio of each structural unit in a polymer can be measured by nuclear magnetic resonance spectroscopy (NMR).
[0069] A polymer having a structural unit derived from isosorbide and a structural unit derived from an alkane diol (for example, a polymer represented by the above formula (A)) can be produced, for example, by reacting isosorbide and an alkane diol in the presence of phosgene to form a carbonate group (—O—(C═O)—O—).
[0070] As isosorbide having an epoxy group, for example, compounds obtained by replacing the hydroxyl group of isosorbide with a glycidyl ether group (compounds represented by the following formula (1-4)) etc. can be cited. These can be used alone or in combination of two or more. Among them, compounds obtained by replacing the hydroxyl group of isosorbide with a glycidyl ether group (compounds represented by the following formula (1-4)) are preferred.
[0071] It should be noted that although isosorbide having an epoxy group also functions as a thermosetting resin described later, in the present invention, isosorbide having an epoxy group is regarded as a raw material having an isosorbide structure. It can be seen that in the present invention, as long as it has an isosorbide structure, it is regarded as a raw material having an isosorbide structure.
[0072]
[0073] Isosorbide having an epoxy group can be produced, for example, by reacting isosorbide with an epihalohydrin such as epichlorohydrin.
[0074] The number average molecular weight of the raw material having an isosorbide structure is preferably 100 to 5000, more preferably 500 to 2000, and even more preferably 700 to 1300. This tends to further improve light transmittance and heat resistance.
[0075] In this specification, the number average molecular weight is a value determined by measuring by gel permeation chromatography (GPC) and converting it into polystyrene.
[0076] The hydroxyl value of the raw material having an isosorbide structure is preferably 50 mgKOH / g to 300 mgKOH / g, more preferably 100 mgKOH / g to 200 mgKOH / g, and further preferably 130 mgKOH / g to 160 mgKOH / g. This has a tendency to further improve light transmittance and heat resistance. It should be noted that in this specification, the hydroxyl value refers to the hydroxyl value described in JIS K 0070: 1992, that is, the number of mg of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of the sample is acetylated.
[0077] The raw material having an isosorbide structure preferably has a biomass carbon content (biomass ratio) of 20% by mass or more, more preferably 40% by mass or more. The larger the biomass ratio, the lower the environmental load, so there is no particular upper limit.
[0078] In 100% by mass of the optical semiconductor encapsulating resin composition, the ratio of the raw material having an isosorbide structure is preferably 5% to 60% by mass, more preferably 10% to 50% by mass, and further preferably 25% to 35% by mass. This tends to further improve light transmittance and heat resistance.
[0079] <<Thermosetting resin>>
[0080] As a thermosetting resin (wherein, excluding raw materials having an isosorbide structure), epoxy resins can be appropriately used. As epoxy resins, epoxy resins with less coloring are preferred, for example, heterocyclic epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins, isocyanuric acid triglycidyl esters, hydantoin epoxy resins, hydrogenated bisphenol A type epoxy resins, aliphatic epoxy resins, glycidyl ether type epoxy resins, cresol novolac type epoxy resins, etc. can be listed. These can be used alone or in combination of two or more. Among them, bisphenol A type epoxy resins, alicyclic epoxy resins, and isocyanuric acid triglycidyl esters are preferred, and alicyclic epoxy resins are more preferred. In addition, bisphenol A type epoxy resins and alicyclic epoxy resins are also preferably used in combination. In addition, epoxy resins without aromatic rings are preferred, and alicyclic epoxy resins and isocyanuric acid triglycidyl esters are more preferred.
[0081] In the present specification, an alicyclic formula (alicyclic structure) refers to a saturated or unsaturated carbon ring structure (preferably a carbon ring having no unsaturated bond in the ring) that does not have aromaticity.
[0082] The ratio of the bisphenol A type epoxy resin in 100% by mass of the epoxy resin is preferably 10% by mass to 50% by mass, and more preferably 20% by mass to 40% by mass. This makes it possible to control the reactivity and adjust the gelation time.
[0083] In 100% by mass of the epoxy resin, the proportion of the epoxy resin without an aromatic ring (preferably the total proportion of the alicyclic epoxy resin and triglycidyl isocyanurate, more preferably the proportion of the alicyclic epoxy resin) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, particularly preferably 95% by mass or more, and may be 100% by mass. Thus, better light transmittance and heat resistance can be obtained.
[0084] In 100% by mass of the optical semiconductor encapsulating resin composition, the bisphenol A type epoxy resin is preferably 5% to 50% by mass, more preferably 3% to 30% by mass, and further preferably 10% to 20% by mass. This allows controlling the reactivity and adjusting the gelation time.
[0085] In 100% by mass of the resin composition for optical semiconductor encapsulation, the proportion of the epoxy resin without an aromatic ring (preferably the total proportion of the alicyclic epoxy resin and triglycidyl isocyanurate, more preferably the proportion of the alicyclic epoxy resin) is preferably 5% by mass to 60% by mass, more preferably 15% by mass to 50% by mass, and further preferably 25% by mass to 40% by mass. This can obtain better light transmittance and heat resistance.
[0086] The resin composition for optical semiconductor encapsulation of the present invention may contain a thermosetting resin other than the epoxy resin.
[0087] In 100% by mass of the thermosetting resin, the proportion of the epoxy resin is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, particularly preferably 60% by mass or more, most preferably 80% by mass or more, most preferably 90% by mass or more, and may be 100% by mass.
[0088] <<Curing Agent>>
[0089] The curing agent is not particularly limited, but is preferably an acid anhydride that produces little coloration in a cured product of the resin composition during or after curing. Examples of the acid anhydride include aromatic polycarboxylic acid anhydrides such as phthalic anhydride, trimellitic anhydride, and pyromellitic anhydride; chain polycarboxylic acid anhydrides such as maleic anhydride; alicyclic polycarboxylic acid anhydrides such as hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, methylnadic anhydride, nadic anhydride, glutaric anhydride, methyltetrahydrophthalic anhydride, dimethyltetrahydrophthalic anhydride, norbornene dicarboxylic anhydride, methylbicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, methylbicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, and cyclopentanetetracarboxylic anhydride; and the like. Among them, alicyclic polycarboxylic acid anhydrides are preferred, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, and tetrahydrophthalic anhydride are more preferred, and hexahydrophthalic anhydride is further preferred.
[0090] In the present specification, an alicyclic polycarboxylic acid anhydride refers to a compound having a carboxylic acid anhydride group and an alicyclic structure.
[0091] The curing agent may be used alone or in combination of two or more.
[0092] As other curing agents, there can be cited metaphenylenediamine, dimethyldiphenylmethane, diaminodiphenyl sulfone, metaphenylenediamine, tetraethylenepentamine, diethylamine, propylamine, etc., which are amine curing agents, phenolic resin curing agents, alicyclic polycarboxylic acids such as cyclohexene dicarboxylic acid, cyclopropane dicarboxylic acid, cyclopropane tricarboxylic acid, cyclobutane dicarboxylic acid, cyclohexane tetracarboxylic acid, and cyclooctane dicarboxylic acid, etc. These can be used alone or in combination of two or more. Among them, alicyclic polycarboxylic acids are preferred, and cyclohexene dicarboxylic acid is more preferred.
[0093] In the present specification, an alicyclic polycarboxylic acid refers to a compound having an alicyclic structure and a plurality of carboxyl groups.
[0094] The amount of curing agent is not particularly limited, for example, relative to 100 parts by mass of thermosetting resin (preferably epoxy resin), preferably 20 parts by mass to 200 parts by mass, more preferably 60 parts by mass to 145 parts by mass. When the amount of curing agent is less than 20 parts by mass, the speed of curing slows down, and when the amount of curing agent is greater than 200 parts by mass, it exists excessively relative to the curing reaction, and therefore may cause a reduction in various physical properties. It should be noted that the ratio of alicyclic polycarboxylic acid anhydride in 100% by mass of curing agent is preferably 80% by mass or more, more preferably 90% by mass or more, more preferably 95% by mass or more, and can be 100% by mass. Thus, there is a tendency to further improve light transmittance and heat resistance.
[0095] <<Antioxidants>>
[0096] The optical semiconductor encapsulation resin composition of the present invention may contain an antioxidant, which tends to provide better heat resistance.
[0097] The antioxidants may be used alone or in combination of two or more.
[0098] Examples of the antioxidant include phenolic antioxidants such as 2,6-di-tert-butyl-p-hydroxytoluene, 2,6-di-tert-butyl-p-cresol, and 2,6-di-tert-butyl-4-ethylphenol; phosphorus-containing antioxidants such as tris(2,4-di-tert-butylphenyl)phosphite, triphenyl phosphite, diphenylisodecylphosphite, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide; and amino antioxidants such as diphenylamine. Among them, phenolic antioxidants and phosphorus-containing antioxidants are preferred.
[0099] The amount of the antioxidant to be added is preferably 0.5 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, further preferably 0.5 to 5 parts by mass, and particularly preferably 0.5 to 3 parts by mass, based on 100 parts by mass of the epoxy resin.
[0100] When the blending amount of the antioxidant is less than 0.5 parts by mass, the heat resistance may be reduced, and when the blending amount of the oxidizing agent is more than 20 parts by mass, the transmittance may be reduced.
[0101] <<Curing Accelerator>>
[0102] The optical semiconductor encapsulation resin composition of the present invention preferably contains a curing accelerator. This tends to accelerate the curing rate or increase the degree of curing. The curing accelerator may be used alone or in combination of two or more.
[0103] Examples of the curing accelerator include tertiary amines such as triethanolamine and dimethylbenzylamine; imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-methyl-4-methylimidazole; organic phosphorus compounds such as tributyl(methyl)indium dimethyl phosphate, tetraphenylindium / tetraphenylborate, and triphenylphosphine; diazabicycloolefin compounds such as 1,8-diazabicyclo[5,4,0]undec-7-ene and 1,5-diazabicyclo[4,3,0]non-5-ene; etc. Among them, tertiary amines are preferred, and dimethylbenzylamine is more preferred.
[0104] The amount of the curing accelerator is not particularly limited, and can be appropriately selected from the range of 0.1 to 5 parts by mass, preferably 0.1 to 3 parts by mass, and more preferably 0.1 to 2 parts by mass, relative to 100 parts by mass of the epoxy resin. When the amount of the curing accelerator is too small, the curing speed slows down and the productivity decreases. On the other hand, when the amount of the curing accelerator is too large, the curing reaction speed is fast, the control of the reaction state becomes difficult, and the reaction variation may occur.
[0105] <<Silane coupling agent>>
[0106] The resin composition for optical semiconductor encapsulation of the present invention preferably contains a silane coupling agent, which can improve adhesion to a substrate or a lead frame.
[0107] As silane coupling agents, for example, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethylethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, etc. can be listed. These can be used alone or in combination of two or more. Among them, mercapto-based silane coupling agents such as 3-mercaptopropyltrimethoxysilane are preferred, and 3-mercaptopropyltrimethoxysilane is more preferred.
[0108] The amount of the silane coupling agent is not particularly limited, but is preferably 0.1 to 20 parts by mass, more preferably 0.2 to 10 parts by mass, and even more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the epoxy resin, so that the epoxy resin can be well and firmly adhered to the substrate or the lead frame.
[0109] <<Other additives>>
[0110] The optical semiconductor encapsulation resin composition of the present invention may contain additives such as lubricants, phosphors for changing the wavelength of light, and inorganic / organic fillers for diffusing light, in addition to the above-mentioned components, as required. These additives may be used alone or in combination of two or more.
[0111] Examples of lubricants include waxes such as stearic acid, magnesium stearate, and calcium stearate; talc, etc. It should be noted that when the lubricant is added, its amount can be appropriately set according to the tableting conditions, for example, preferably set to 0.1% to 0.4% by mass of the entire resin composition.
[0112] As a phosphor that changes the wavelength of light and an inorganic / organic filler that diffuses light, examples include silica powders such as quartz glass powder, talc, fused silica powder and crystalline silica powder, alumina, silicon nitride, aluminum nitride, silicon carbide, carbon black, etc. These can be used alone or in combination of two or more. It should be noted that in the case of phosphors and inorganic / organic fillers, the amount of the phosphors can be appropriately set according to the molding conditions. Specifically, in the case of phosphors, the amount of the phosphors can be appropriately set from the range of 1% to 60% by mass of the entire resin composition. On the other hand, in the case of fillers (organic / inorganic) that scatter light, the fillers that scatter light can be appropriately set from the range of 0.5% to 25% by mass of the entire resin molding.
[0113] <<Reaction Products>>
[0114] The resin composition for optical semiconductor encapsulation of the present invention may contain a reaction product of each compounding ingredient such as a reaction product of a thermosetting resin and a curing agent.
[0115] <Method for producing resin composition for optical semiconductor encapsulation>
[0116] The method for producing the optical semiconductor encapsulating resin composition of the present invention is not particularly limited as long as it is a method capable of kneading and dispersing the above-mentioned components, but it is preferably heat-treated to form a B-stage state (semi-cured state).
[0117] The method for producing the optical semiconductor encapsulation resin composition of the present invention includes, for example, a method comprising: kneading a thermosetting resin, a bio-derived raw material, a curing agent, and a curing accelerator to obtain a curable resin composition; and heat-treating the curable resin composition.
[0118] There is no particular limitation on the kneading method, and for example, a method using an extruder can be cited. There is no particular limitation on the kneading temperature, and it can be appropriately changed according to the properties of the thermosetting resin, or the temperature can be set higher to allow the reaction to proceed during kneading. Specifically, it is preferably 80°C to 150°C, and more preferably 110°C to 130°C.
[0119] The shape of the curable resin composition obtained by kneading is not particularly limited, and examples thereof include a film shape, a sheet shape, a pellet shape, and a block shape.
[0120] The thickness of the curable resin composition obtained by kneading is not particularly limited, but is preferably 1 mm to 30 mm, more preferably 2 mm to 20 mm, and further preferably 2 mm to 10 mm. When the thickness of the curable resin composition is less than 1 mm, the thickness is thin and is easily affected by moisture absorption. When the thickness of the curable resin composition is greater than 30 mm, it takes time to cool, and there is a tendency for the reaction to change due to internal heat storage.
[0121] The curable resin composition obtained by kneading is heat-treated to obtain a B-stage (semi-cured) optical semiconductor encapsulation resin composition. The heat treatment temperature is not particularly limited, and is preferably 25°C to 100°C, and more preferably 60°C to 80°C. When the heat treatment temperature is less than 25°C, the curing reaction is slow and there is a tendency for reduced productivity. When the heat treatment temperature is greater than 100°C, the curing reaction is fast and there is a tendency for it to be difficult to terminate the reaction under a specified reaction state. There is no particular limitation on the heat treatment time, and it can be appropriately changed according to the characteristics of the thermosetting resin.
[0122] The optical semiconductor encapsulating resin composition in a B-stage state (semi-cured state) obtained by heat treatment is preferably subjected to the following steps.
[0123] A step of pulverizing and / or granulating the heat-treated curable resin composition (resin composition for optical semiconductor encapsulation in a B-stage state (semi-cured state)) to obtain a granular curable resin composition.
[0124] When pulverizing is performed, the heat-treated resin composition is pulverized to obtain a granular resin composition. The pulverization can be performed using a ball mill, a turbo mill, a hammer mill, a cutter mill, or the like.
[0125] When granulation is performed, the heat-treated resin composition is granulated to obtain a granular resin composition. Before granulation, the resin composition may be pulverized using a ball mill, a turbo mill, or the like. The granulation method is not particularly limited, and examples thereof include a method using a dry compression granulator.
[0126] The average particle size of the granules obtained by pulverization and / or granulation is not particularly limited, but is preferably 1 μm to 5000 μm, more preferably 100 μm to 2000 μm. When the average particle size of the granules is larger than 5000 μm, the compressibility tends to decrease.
[0127] The step of obtaining the granular curable resin composition is preferably a step of granulating the heat-treated curable resin composition (B-stage (semi-cured) optical semiconductor encapsulating resin composition) to obtain the granular curable resin composition.
[0128] For the optical semiconductor encapsulation resin composition of the present invention obtained by the above-mentioned preparation method, when a cured body (size: cylindrical with a diameter of 50 mm × a thickness of 1 mm) is prepared by the following method, the linear transmittance at a wavelength of 400 nm is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, particularly preferably 80% or more, most preferably 90% or more, and most preferably 95% or more, and the upper limit is not particularly limited. This can more appropriately suppress the degradation caused by light.
[0129] (Method for producing a solidified body)
[0130] The heated and molten resin composition was extruded into a molding die heated to 150°C±5°C by transfer molding under pressure using a transfer molding machine, and cured for 4 minutes without any voids inside to obtain a uniform cured body. The uniform cured body was then taken out of the mold and heated at 150°C for 3 hours in a dryer to completely cure it, thereby obtaining a cured body.
[0131] For the resin composition for optical semiconductor encapsulation of the present invention obtained by the above-mentioned preparation method, the linear transmittance at a wavelength of 400nm after the cured body (size: cylindrical with a diameter of 50mm×thickness of 1mm) obtained by the above-mentioned method is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, particularly preferably 80% or more, most preferably 90% or more, and most preferably 93% or more, and the upper limit is not particularly limited. Thus, it is possible to more appropriately suppress the degradation caused by light and the reduction of heat resistance.
[0132] The reflow soldering is performed using the cured product in a reflow furnace under the conditions of a peak temperature of 265° C. for 10 seconds each time.
[0133] The linear transmittance is obtained by measuring the transmission spectrum of the cured product at a wavelength of 400 nm using a spectrophotometer. The transmission spectrum is measured in a direction perpendicular to the bottom surface (or top surface) of the sample.
[0134] In order to prepare a resin composition for optical semiconductor encapsulation having the above-mentioned linear transmittance and the linear transmittance after three reflows within the above-mentioned ranges, the composition can be prepared according to the following guidelines.
[0135] (1) Using a raw material having an isosorbide structure: The isosorbide structure is an alicyclic structure and therefore has excellent light transmittance, which can suppress degradation due to light and also has excellent heat resistance.
[0136] (2) Use of compounds with few aromatic rings such as bisphenol structure. This is because aromatic rings absorb light in the short wavelength region and reduce heat resistance.
[0137] (3) Even when using a compound having an aromatic ring, a compound without a conjugated structure is used. This is because: a compound having an aromatic ring and a conjugated structure has a large light absorption in the range of 280nm to 320nm, but a compound having an aromatic ring but no conjugated structure has almost no light absorption in the entire range of 280nm to 400nm.
[0138] (4) Using a compound containing cyclohexane This is because a compound containing cyclohexane has almost no light absorption in the entire range of 280 nm to 400 nm.
[0139] Regarding the resin composition for optical semiconductor encapsulation of the present invention obtained by the above-mentioned production method, the glass transition temperature of the cured product (size: cylindrical with a diameter of 50 mm and a thickness of 1 mm) obtained by the above-mentioned method is preferably 0° C. or higher, more preferably 70° C. to 200° C., further preferably 90° C. to 180° C., and particularly preferably 100° C. to 160° C. As a result, the resistance to temperature cycle tests and yellowing is improved.
[0140] In this specification, the glass transition temperature of a cured product is measured by the method described in Examples.
[0141] The resin composition for optical semiconductor encapsulation of the present invention obtained by the above-mentioned production method etc., the Shore D hardness of the cured product (size: cylindrical shape with a diameter of 50 mm×a thickness of 1 mm) obtained by the above-mentioned method is preferably 50 to 100, more preferably 60 to 100, and even more preferably 70 to 100. This can improve the impact resistance.
[0142] In this specification, the Shore D hardness of a cured product is measured by the method described in Examples.
[0143] In order to prepare the resin composition for optical semiconductor encapsulation having the glass transition temperature and the Shore D hardness both within the above ranges, the composition can be prepared according to the following guidelines.
[0144] (1) Using a material having an alicyclic and rigid chemical structure is because the glass transition temperature can be adjusted thereby.
[0145] (2) Use of a polyfunctional alicyclic epoxy material is because the glass transition temperature can be adjusted thereby.
[0146] The optical semiconductor encapsulation resin composition of the present invention obtained by the above-mentioned preparation method is subjected to the molding process at a mold temperature of 150° C. and a molding pressure of 970 kgf / cm according to EMMI (Epoxy Molding Materials Research Institute) Standard 1-66. 2 The spiral flow length measured under the conditions of 120s curing time and 2.0cm / s injection speed is preferably 50cm to 350cm, more preferably 140cm to 300cm. When the spiral flow length is too short, there is a tendency for the filling property in the mold to decrease, and when the spiral flow length is too long, it may leak out of the mold and cause resin burrs.
[0147] The optical semiconductor encapsulation resin composition of the present invention obtained by the above-mentioned preparation method is subjected to the molding process at a mold temperature of 150° C. and a molding pressure of 970 kgf / cm according to EMMI (Epoxy Molding Materials Research Institute) Standard 1-66. 2 The gelation time measured under the conditions of 10 to 60 seconds, 120 seconds of curing time, and 2.0 cm / s of injection speed is preferably 10 to 60 seconds, and more preferably 20 to 50 seconds. When the gelation time is too short, curing is too fast, so filling into the mold becomes difficult, and when the gelation time is too long, curing is too slow, and there is a tendency for productivity to decrease.
[0148] In the present specification, the spiral flow length and the gel time are measured by the methods described in Examples.
[0149] In order to prepare the resin composition for optical semiconductor encapsulation having the spiral flow length and the gel time both within the above ranges, the composition can be prepared according to the following guidelines.
[0150] (1) A composition within the above range can be prepared by subjecting the resin composition to a heat treatment at 40° C. to 70° C. The composition can be prepared more easily when the treatment is conducted at a lower temperature.
[0151] The viscosity of the optical semiconductor encapsulating resin composition of the present invention obtained by the above-mentioned production method is preferably 50 dPa·s to 300 dPa·s, more preferably 80 dPa·s to 150 dPa·s. This ensures the filling property into the mold.
[0152] In this specification, the above-mentioned viscosity is measured by the method described in Examples.
[0153] In order to prepare the resin composition for optical semiconductor encapsulation having the viscosity within the above range, the composition can be prepared according to the following guidelines.
[0154] (1) A composition within the above range can be prepared by subjecting the resin composition to a heat treatment at 40° C. to 70° C. The composition can be prepared more easily when the treatment is conducted at a lower temperature.
[0155] The resin composition for optical semiconductor encapsulation of the present invention is suitably used for transfer molding.
[0156] <Resin molded article for optical semiconductor encapsulation>
[0157] Examples of the resin molded product for optical semiconductor encapsulation of the present invention include a tablet shape, a sheet shape, and the like, and by molding the product so as to cover an optical semiconductor element constituting an optical semiconductor device, the element can be encapsulated.
[0158] When the optical semiconductor encapsulating resin molded article is in the form of a tablet, its volume is not particularly limited, but is preferably 1 cm 3 ~100cm 3 , more preferably 10 cm 3 ~100cm 3 .
[0159] The method for producing a resin molded product for an optical semiconductor package of the present invention includes, for example, a step of molding the granular resin composition obtained by the step of obtaining the granular curable resin composition in addition to the above-mentioned steps.
[0160] The resin molded product for optical semiconductor encapsulation of the present invention is obtained by molding the resin composition for optical semiconductor encapsulation of the present invention. Thus, a resin molded product for optical semiconductor encapsulation containing the resin composition for optical semiconductor encapsulation of the present invention is obtained. As the molded product, tablets and thin sheets can be listed, and as the molding method, tablet molding to obtain tablets, extrusion molding to obtain thin sheets, etc. can be listed. The obtained molded product becomes an environmentally friendly high-quality molded product.
[0161] The optical semiconductor encapsulating resin composition is molded to obtain an optical semiconductor encapsulating resin molded product. The optical semiconductor encapsulating resin composition and the optical semiconductor encapsulating resin molded product have basically the same composition.
[0162] In the case where the molded product is in the form of a tablet, the conditions for tableting are appropriately adjusted according to the composition of the resin composition for optical semiconductor encapsulation, etc., and it is usually appropriate to set the compression rate during tableting to 90% to 96%. That is, this is because: when the compression rate is less than 90%, the density of the tablet may become low and it may be easy to break. On the contrary, when the compression rate is greater than 96%, cracks may occur during tableting, and defects or bends may occur during demolding.
[0163] <Optical semiconductor packaging material, optical semiconductor device>
[0164] The optical semiconductor encapsulation resin molded article of the present invention is used to encapsulate an optical semiconductor element by a molding method such as transfer molding, thereby producing an optical semiconductor device. That is, the optical semiconductor encapsulation resin molded article of the present invention becomes an optical semiconductor encapsulation material that resin-encapsulates an optical semiconductor element by molding such as transfer molding. It can be seen that the optical semiconductor encapsulation material of the present invention is obtained by molding the optical semiconductor encapsulation resin molded article of the present invention.
[0165] In this specification, the optical semiconductor encapsulating material refers to a member which is formed so as to cover an optical semiconductor element constituting an optical semiconductor device and encapsulates the element.
[0166] The optical semiconductor encapsulation resin composition and the optical semiconductor encapsulation resin molded product of the present invention are environmentally friendly, and therefore the optical semiconductor encapsulation material obtained by molding the optical semiconductor encapsulation resin composition and the optical semiconductor encapsulation resin molded product of the present invention is an environmentally friendly high-quality optical semiconductor encapsulation material.
[0167] The optical semiconductor device of the present invention comprises: an optical semiconductor element; and an optical semiconductor encapsulating material of the present invention encapsulating the optical semiconductor element. The optical semiconductor device of the present invention comprises the optical semiconductor encapsulating material of the present invention, and is therefore an environmentally friendly, high-quality optical semiconductor device.
[0168] When the optical semiconductor encapsulation resin composition and the optical semiconductor encapsulation resin molded product of the present invention are made into a cured product, the light transmittance is excellent, and as a result, the degradation caused by light can be suppressed, and the heat resistance is also excellent. Therefore, the optical semiconductor encapsulation resin composition and the optical semiconductor encapsulation resin molded product of the present invention can be appropriately used as an encapsulation material for a light-emitting element or an encapsulation material for a light-emitting device having a light-emitting element, and can be more appropriately used as an encapsulation material for a light-emitting diode or an encapsulation material for a light-emitting device having a light-emitting diode.
[0169] Likewise, the optical semiconductor device of the present invention is preferably a light-emitting device having a light-emitting element, and more preferably a light-emitting device having a light-emitting diode.
[0170] As light-emitting elements, for example, there can be listed: UV light-emitting elements such as UV-A (315nm~400nm) light-emitting elements, UV-B (280nm~315nm) light-emitting elements, and UV-C (100nm~280nm) light-emitting elements; and visible light-emitting elements such as R (red) light-emitting elements, G (green) light-emitting elements, and B (blue) light-emitting elements.
[0171] In addition, the light emitting element is preferably a light emitting diode.
[0172] In addition, as the light emitting diode, it can be used in the form of a shell type, a chip type (surface mount type), etc., preferably a chip type, and more preferably a chip LED.
[0173] Example
[0174] Next, examples and comparative examples will be described. However, the present invention is not limited to the following examples.
[0175] The materials used are shown below.
[0176] Plant-derived biodiol 1: Benebiol HS0850H manufactured by Mitsubishi Chemical Corporation (a polymer represented by the above formula (A), in 100% by mass of the polymer, the ratio of the structural unit derived from isosorbide: 44% by mass, the ratio of the structural unit derived from 1,6-hexanediol: 56% by mass, number average molecular weight: 800, hydroxyl value: 140 mgKOH / g, biomass ratio: 44% by mass (a diol using plant-derived isosorbide))
[0177] Plant-derived biodiol 2: BioPTMG650 manufactured by Mitsubishi Chemical Corporation (environmentally friendly polytetramethylene ether glycol using plant-derived raw materials, number average molecular weight: 650, hydroxyl value: 160 mgKOH / g to 187 mgKOH / g)
[0178] Petroleum-derived glycol 1: P-700 (polyethylene glycol) manufactured by ADEKA
[0179] Petroleum-derived glycol 2: NPG (neopentyl glycol) manufactured by Mitsubishi Gas Chemical Trading Co., Ltd.
[0180] Epoxy resin 1: Epokukdo YD-012W (bisphenol A type epoxy resin) manufactured by Kukdo Chemical Co., Ltd.
[0181] Epoxy resin 2: TEPIC-S (triglycidyl isocyanurate (epoxy equivalent 100) manufactured by Nissan Chemical Co., Ltd.)
[0182] Epoxy resin 3: EHPE3150 manufactured by Daicel Corporation (alicyclic epoxy resin (epoxy equivalent 180))
[0183] Curing agent 1: RIKACID MH-700G (hexahydrophthalic anhydride) manufactured by Shin Nippon Chemical Co., Ltd.
[0184] Curing agent 2: RIKACID HH (HHPA, hexahydrophthalic anhydride) manufactured by Shin Nippon Chemical Co., Ltd.
[0185] Antioxidant 1: H-BHT (2,6-di-tert-butyl-p-cresol) manufactured by Honshu Chemical Industry Co., Ltd.
[0186] Antioxidant 2: HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) manufactured by Sanko Co., Ltd.
[0187] Antioxidant 3: TPP-R (triphenyl phosphite) manufactured by Daihachi Chemical Industry Co., Ltd.
[0188] Silane coupling agent: KBM803 (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Silicone Co., Ltd.
[0189] Curing accelerator 1: N,N-dimethylbenzylamine manufactured by Tokyo Chemical Industry Co., Ltd.
[0190] Curing accelerator 2: Hishicolin PX4MP (methyltributylphosphonium iodide) manufactured by Nippon Chemical Industry Co., Ltd.
[0191] Examples and Comparative Examples
[0192] The raw materials were mixed at 100-150° C. in the amounts shown in Table 1. The curable resin composition obtained by mixing was heat-treated to obtain a B-stage (semi-cured) optical semiconductor encapsulation resin composition. The heating melting temperature, heat treatment temperature and heat treatment time were appropriately changed according to the characteristics of the thermosetting resin.
[0193] The optical semiconductor encapsulation resin compositions prepared in the Examples and Comparative Examples were used to perform evaluations by the following methods.
[0194] <Preparation of Test Specimen (Cured Body)>
[0195] The optical semiconductor encapsulation resin composition (heated and melted resin composition) prepared as described above was extruded into a molding die heated to 150°C±5°C under pressure using a transfer molding machine, and cured for 4 minutes without voids inside to obtain a uniform cured body, thereby preparing a test piece cured product (size: cylindrical with a diameter of 50 mm×thickness of 1 mm). The test piece cured product was heated at 150°C for 3 hours to completely complete the curing, thereby obtaining a test piece.
[0196] <Linear transmittance>
[0197] First, a quartz cell was filled with liquid paraffin manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and a baseline was measured using a spectrophotometer V-670 manufactured by JASCO Corporation. Then, the test piece prepared above (size: cylindrical with a diameter of 50 mm and a thickness of 1 mm) was immersed in the liquid paraffin in the quartz cell, and the light transmittance (linear transmittance) at a wavelength of 400 nm was measured at room temperature (25° C.) using a spectrophotometer (V-670 manufactured by JASCO Corporation) while suppressing light scattering on the surface of the sample. It should be noted that the transmission spectrum was measured in a direction perpendicular to the bottom surface of the sample (thickness direction).
[0198] <Glass transition temperature (Tg)>
[0199] Using RSA-II manufactured by RHEOMETRIC SCIENTIFIC, the storage modulus E' and loss modulus E'' of the test piece prepared above were obtained under the measurement conditions of tensile mode, frequency of 1 Hz, scanning temperature of 0 to 270°C, and heating rate of 10°C / min. Based on them, the curve of tanδ (=E'' / E') was calculated, and the glass transition temperature (Tg) was calculated as the peak temperature of tanδ.
[0200] <Reflow>
[0201] The test piece prepared above was passed through a reflow oven (peak 265°C x 10 seconds) three times. For the test piece after the three reflows, the linear transmittance (linear transmittance at a wavelength of 400nm after the three reflows at 265°C) was measured according to the method described in the above <Linear Transmittance>. The higher the linear transmittance at a wavelength of 400nm after the three reflows at 265°C (the higher the maintenance rate of the linear transmittance before and after the reflow), the better the heat resistance.
[0202] <Shore D Hardness>
[0203] The hardness of the test piece prepared above was measured at 25°C using a Shore D hardness meter.
[0204] <Spiral flow length, gelation time>
[0205] The resin composition for optical semiconductor encapsulation prepared above was adjusted for reaction degree at 40° C. to 80° C., and then pulverized and tablet-formed to prepare a resin tablet for optical semiconductor encapsulation.
[0206] The spiral flow length and gelation time are in accordance with EMMI (Epoxy Molding Materials Research Institute) standard 1-66, at a mold temperature of 150°C and a molding pressure of 970kgf / cm 2, solidification time 120s, injection speed 2.0cm / s. Specifically, the obtained tablets are coarsely crushed using a flowability measuring device, and the powder that has passed through a sieve with an opening diameter of 5mm is placed in a container maintained at 150°C and pressed by pressing the plunger at a constant speed. The spiral flow length is calculated by measuring the displacement of the plunger and its time. The gelation time is measured as the time from the start of the measurement to the time when the plunger speed reaches a constant value.
[0207] <Viscosity>
[0208] According to EMMI (Epoxy Molding Materials Research Institute) standard 1-66, at a mold temperature of 150°C and a molding pressure of 970kgf / cm 2 , curing time 120s, injection speed 2.0cm / s. Specifically, the obtained tablets were coarsely crushed using a flowability measuring device, and the powder that passed through a sieve with an opening diameter of 5mm was placed in a container maintained at 150°C, and pressed by pressing the plunger at a constant speed. The melt viscosity calculated from the measured torque was plotted against time, and the value b obtained by subtracting the minimum melt viscosity from the index viscosity 800dPa·s, and the time a from the minimum melt viscosity to the time when it reaches 800dPa·s again during the curing process were calculated.
[0209] <Crushability>
[0210] A weight of 1 kg was dropped from a height of 30 cm onto the optical semiconductor encapsulation resin composition (thickness 5 cm) prepared above to determine whether the composition was broken. If the composition was broken, the crushability was judged as 0, and if the composition was not broken, the crushability was judged as ×.
[0211] <Tableting properties (tabletting)>
[0212] The above-prepared optical semiconductor encapsulation resin composition was adjusted to a reactivity at 40 to 80°C, and was crushed and tableted to prepare a resin tablet for optical semiconductor encapsulation. The fracture and defect of the prepared tablets were visually evaluated. In the case where no fracture and defect occurred, the tableting property was judged as 0, and in the case of fracture and defect and fusion, the tableting property was judged as ×.
[0213]
[0214] The experimental results shown in Table 1 show that the Examples using the optical semiconductor encapsulating resin composition having a biomass ratio of 10 mass % or more are environmentally friendly and have the characteristics required as an optical semiconductor encapsulating resin composition.
[0215] Industrial Applicability
[0216] The present invention relates to a resin composition for optical semiconductor encapsulation and an optical semiconductor encapsulation resin molded product used for encapsulating an optical semiconductor element, and can be used for production of an optical semiconductor encapsulation material and an optical semiconductor device.
Claims
1. A resin composition for optical semiconductor encapsulation, wherein: The resin composition for optical semiconductor encapsulation has a biomass ratio of 10% by mass or more.
2. The resin composition for optical semiconductor encapsulation according to claim 1, wherein The resin composition for optical semiconductor encapsulation contains a plant-derived diol.
3. The resin composition for optical semiconductor encapsulation according to claim 2, wherein The diol is a diol having hydroxyl groups at both ends of the main chain.
4. The resin composition for optical semiconductor encapsulation according to claim 2, wherein The diol is a polymer.
5. The resin composition for optical semiconductor encapsulation according to claim 1 or 2, wherein When a cured product (size: cylindrical, 50 mm in diameter x 1 mm in thickness) is prepared by the following method, the linear transmittance at a wavelength of 400 nm is 50% or more. (Method for producing a solidified body) Using a transfer molding machine, the heated and molten resin composition is extruded into a molding mold heated to 150°C±5°C by transfer molding under pressure, and is cured for 4 minutes without any voids inside to obtain a uniform cured body; then the uniform cured body is taken out from the mold, and is heated in a dryer at 150°C for 3 hours to completely cure it, thereby obtaining a cured body.
6. The resin composition for optical semiconductor encapsulation according to claim 1 or 2, wherein The cured product (size: cylindrical shape with a diameter of 50 mm and a thickness of 1 mm) obtained by the above method was subjected to reflow three times at 265° C., and the linear transmittance at a wavelength of 400 nm was 50% or more.
7. The resin composition for optical semiconductor encapsulation according to claim 1 or 2, wherein The glass transition temperature of the cured product (size: cylindrical shape with a diameter of 50 mm and a thickness of 1 mm) obtained by the above method is 0°C or higher.
8. The resin composition for optical semiconductor encapsulation according to claim 1 or 2, wherein The resin composition for optical semiconductor encapsulation is used for transfer molding.
9. A resin molded article for optical semiconductor encapsulation, wherein: The optical semiconductor encapsulation resin molded article comprises the optical semiconductor encapsulation resin composition according to claim 1 or 2.
10. An optical semiconductor packaging material, wherein: The optical semiconductor encapsulating material is obtained by molding the optical semiconductor encapsulating resin molded product according to claim 9 .
11. An optical semiconductor device, wherein: The optical semiconductor device comprises: an optical semiconductor element; and the optical semiconductor encapsulating material according to claim 10 for encapsulating the optical semiconductor element.
Citation Information
Patent Citations
Encapsulating resin composition for surface-mounted discrete devices in LED displays and its uses
JP2021528503A